Employee Performance Measurements at ‘Aisyiyah Klaten Hospital using the Human Resources Scorecard approach - Siti Kundariyah; Heru Kurnianto Tjahjono; Qurratul Aini; Winny Setyonugroho (Disease Prevention and Public Health Journal, 2021)
Background: The rapid development of health services is a challenge for hospitals in facing the increasingly open and accessible competition. Good human resource management is needed to increase the productivity of an organization. One of the strategies to increase productivity and improve human resource management is to use an integrated and comprehensive employee performance measurement. This research measured employee performance using the Human Resources Scorecard (HRSC) approach based on several conditions. HRSC is a Balanced Scorecard with a Human Resources (HR) approach where Key Performance Indicators (KPI) are based on 4 (four) perspectives: Financial Perspective, Customer Perspective, Internal Business Process Perspective, and Learning and Growth Perspective. Method: This study used a quantitative approach with a cross-sectional survey research design. Data collection methods included questionnaires, document review, and Consensus Decision Making Group (CDMG). The research population was 256 employees of the ‘Aisyiyah Hospital Klaten.  Samples were determined using non-probability sampling technique with a purposive sampling method of 100 respondents. Results: The results showed that overall employee performance was good, with a score of 4.03. Based on Key Performance Indicators for each perspective, the internal business process perspective of employee performance was very good, with a score of 1.24. The financial perspective of employee performance was good with a score of 0.8, while the customer perspective of employee performance was good, with a score of 1.19. Finally, the learning and growth perspective of employee performance was good, with a score of 0.8. Conclusion: With the HRSC approach, the overall performance results of the ‘Aisyiyah Klaten Hospital employees were good.